Differential expression of myosin heavy chain isoforms in cardiac segments of gnathostome vertebrates and its evolutionary implications - López-Unzu, Miguel A.; Durán-Boyero, Ana Carmen; Soto-Navarrete, María Teresa; Sans-Coma, Valentín; Fernández-Corujo, Borja (BioMed Central (Springer Nature), 2019)
Immunohistochemical studies of hearts from the lesser spotted dogfish, Scyliorhinus canicular (Chondrichthyes) revealed that the pan-myosin heavy chain (pan-MyHC) antibody MF20 homogeneously labels all the myocardium, while the pan-MyHC antibody A4.1025 labels the myocardium of the inflow (sinus venosus and atrium) but not the outflow (ventricle and conus arteriosus) cardiac segments, as opposed to other vertebrates. We hypothesized that the conventional pattern of cardiac MyHC isoform distribution present in most vertebrates, i.e. MYH6 in the inflow and MYH7 in the outflow segments, has evolved from a primitive pattern that persists in Chondrichthyes. In order to test this hypothesis, we conducted protein detection techniques to identify the MyHC isoforms expressed in adult dogfish cardiac segments and to assess the pan-MyHC antibodies reactivity against the cardiac segments of representative species from different vertebrate groups. The cardiac inflow and outflow segments of the dogfish show predominance of fast- and slow-twitch MyHC isoforms respectively, what can be considered a synapomorphy of gnathostomes. The myocardium of the dogfish contains two isomyosins (MYH2 and MYH7B) not expressed in the adult heart of other vertebrates. We propose that these isomyosins lost their function in cardiac contraction during the evolution of gnathostomes, the later acquiring a regulatory role in myogenesis through its intronic miRNA. Loss of MYH2 and MYH7B expression in the heart possibly occurred before the origin of Osteichthyes, being the latter reacquired in polypteriforms. We raise the hypothesis that the slow tonic MYH7B facilitates the peristaltic contraction of the conus arteriosus of fish with a primitive cardiac anatomical design and of the vertebrate embryo.
Keywords: Proteínas musculares; Condrictios; Gnathostomes; Myocardium; Myosin heavy chain; MYH2; MYH7B